(3Odjd QjGVI GdSHGMI (B- ( (3GdLRA GdGhd (B)s - (3GdaGJM h LOj eUWais; (3WGQb UdGM aVdi s ((3OGQ GdgOi ddfTQ h GdJhRjYs, 1999)
(3d Y (B662 (3GdcJGH jYQV TQMG hGajG dG SS hGdbhGYO GdYdejI GdJj JQJcR YdjgG Jdc GdQjGVI hGdJj GSJeOJ HOhQgG ef GdYdhe GdWHjYjI hGdEfSGfjI cYde GdMQcI hYde GdejcGfjcG hYde hXGFa GdCYVGA hYde GdJTQjM aGdOdjd jJVef GdCSS GdJYdjejI hGdJQHhjI hbhGYO GdCef GdNGUI HQjGVI GdSHGMI(B.s